Alternativas de Gestión RCD de la construcción de la Vía que comunica a Hidroeléctrica Ituango (2021)
A hydroelectric power plant is responsible for converting the power of water into electric energy; in order to take advantage of the power of these, large hydraulic infrastructures are built whose function is to exploit to the maximum the strength of this resource, which is renewable and emission-free (iberdrola, 2017). Knowing this, in Colombia the construction of a hydroelectric power plant called HidroItuango was proposed, which could be considered as the pride of Civil engineering in Antioquia and Colombia (Semana, 2018).